Dynamic force spectroscopy and biomolecular recognition - Bizzarri, Anna Rita.; Cannistraro, Salvatore (Boca Raton, FL : CRC Press, 2012)
'Molecular recognition or biorecognition is the heart of all biological interactions. Originating from protein stretching experiments, dynamical force spectroscopy allows for the extraction of detailed information on the unbinding process of biomolecular complexes. It is becoming progressively more important in biochemical studies and is finding wider applications in areas such as biophysics and polymer science. This book covers the most recent ideas and advances in the field of DFS applied to biorecognition. Leading experts in the field offer their perspectives on such important topics as atomic force microscopy, force spectroscopy, interaction geometries. and immobilization strategies. Provides in-depth discussion of dynamical force spectroscopy. Covers the major features of biorecognition processes, the basic principles of DFS, and its application to biological complexes. Presents an extensive treatment of theoretical models, data analysis, and the experimental procedures. Includes an updated literature review'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Molecular spectroscopy; Molecular recognition